STELLAR ABUNDANCE. FROM QUANTITY TO QUALITY? - Yushchenko, A. V.; Gopka, V. F. (Одеські астрономічні публікації, 2017)
We present the overview of chemical compositions of the atmospheres of seven stars with the most detailed abundance patterns -- the Sun, Przybylski's star, HD221170, Sirius, Procyon, ζCyg, δSct. The abundance pattern of the Sun is 73 chemical elements, for other stars (except HD221170) -- more than 50 elements. A big quantity of known abundances permits to find a qualitatively new results. The lines of radioactive elements with short decay-time are found in the spectrum of Przybylski's star -- Tc, Pm, and elements with atomic numbers 84<=Z<= 99. The abundances of heaviest elements in old halo star HD221170 permit us to show that it is not correct to use the ratio's of radioactive elements for determination of the age of the stars. The abundance patterns of barium star ζCyg and Sirius A can be explained by mass transfer in the binary system. The chemical composition of Procyon is solar, only Te is overabundant by 0.5 dex. Te is located at one of the peaks of r-process in the standard abundance pattern. The abundance pattern of δ Sct appears to be similar to that of δ Del type stars.